Prevalence, correlates and under-diagnosis of clinical depression among adults on highly active antiretroviral therapy in a Tertiary Health Institution in northeastern Nigeria - Abdu Wakawa Ibrahim; Mohammed Said Jidda; Musa Abba Wakil; Isa Bukar Rabbebe; Asuku Beida Omeiza; Haruna Yusuph; Adegboyega Ogunlesi; Umar Garba Suleiman (AOSIS, 2014)
Clinical depression is a highly debilitating illness, which is often under-diagnosed and negatively impacts on the quality of life of its sufferers. When it co-exists with other medical conditions, its effect is even more incapacitating. Undiagnosed depression in the context of HIV infection leads to accelerated decline in CD4+ cell counts with concomitant increase in the viral load and poor adherence to the antiretroviral medications which lead to viral mutation and the evolution of resistant strains. This study examined the prevalence of depression, its correlates and the frequency of the diagnosis of the condition among HIV+ subjects on highly active antiretroviral therapy (HAART) by the internists and general physicians at the University of Maiduguri Teaching Hospital in Northeastern Nigeria. Three hundred and fifty representative samples of HIV+ adults on HAART were drawn from the Antiretroviral Therapy Clinic of the Institution. Diagnosis of depression was made using the International Classification of Diseases-10 criteria based on Composite International Diagnostic Interview generated data. Socio-demographic and clinical variables were also analyzed for their correlation with depression in the subjects. About 20% of the respondents were diagnosed with clinical depression and no diagnosis of the condition was hitherto entertained in all the respondents. The independent determinants of depression in the participants were: female gender [odds ratio (OR)=3.87 (95% confidence interval, CI: 2.089-7.183)], past history of psychiatric illness [OR=43.81 (95% CI: 9.731-197.30)] and family history of psychiatric illness in first-degree relatives of the subjects [OR=14.364 (95% CI=5.327- 38.729)]. Depression is a relatively common psychiatric condition among adults on HAART, there is therefore the need for routine screening of this condition among HIV+ subjects in order to optimize patient care and improve clinical outcomes.